(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In these lines we mean to express that State’s legislation, even legislation passed to fight acts of extreme violence like terrorism, has to be respectful with the fundamental rights; The response to terrorism can only base its legitimacy in a scrupulous respect to legality and to the guarantees and rights of all citizens. In the peace process, in which our country is still involved and will be till the ending of violence isreached, the Estate has to convince the politic opponent that resort to arms is notnecessary to be heard, to be able to participate in the political system.